Penggunaan Jodoushi dan Keiyoushi dalam Kalimat pada Komik Doraemon Seri 25-35 - Frieska Sekar Nadya (Bina Nusantara University, 2009)
Every language in many countries has its own uniqueness to express wish. In Indonesian, the word “ingin” means want to, or wish to. But in Japanese, there are two classes of word, both have meaning of want or wish. They are jodoushi「～たい」and keiyoushi「ほしい」. These two classes of word usually people find when learning Japanese, especially when reading Japanese comics for children. Therefore, in order to be able to differ the use of those two classes of word and the use of their sentences pattern, as well as the analysis, this research uses Doraemon vol.25-35. As for analyzing all the data, the use of theories from Tomita Takayuki, Seichi Makino and Michio Tsutsui, Naomi Hanaoka McGloin, and also Fumiko Koide will suit them respectively.